MOBILITY, LOCAL IDENTITY AND SUSTAINABILITY OF THE CIRENDEU INDIGENOUS COMMUNITY IN WEST JAVA - Nur Malahayati Sukma, Fajriana; Yuliar, Sonny (Universitas Kristen Satya Wacana, 2025)
ABSTRACT In the literature, it is common to view indigenous peoples in terms of places and territories, local cultures, and unique origins. Such studies go further to identify knowledge and wisdom, and to address the question of sustainability of indigenous peoples, in terms of localities. What seems to be lacking in this spatial view is attention to motions. The aim of this brief article is to bring the mobilities paradigm to the literature on indigenous peoples by presenting a case study. The empirical question that guides our research is how the locality of indigenous peoples be assembled and maintained. Our research addresses this question by examining the localizing factors that form the Cireundeu Village’s indigenous community in Cimahi, West Java. This community originated from the expansion of Kasepuhan Sunda Wiwitan Cigugur, Kuningan. We employ case study method to gather and analyze empirical data and make use of relevant information from secondary sources. Our findings indicate that there are circulations of things, people and information that form and maintain the locality of Cireundeu’s indigenous people. Among these are ideas, technical skills and knowledge. While there is boundary that defines inside and outside, this boundary is maintained through circulations. The capacity of Cireundeus’s indigenous people to adapt to changes seems to develop from their mobilities, instead of reliance on local fixities. With the findings of this research, we seek to contribute to the debates between spatial turns and mobility turns in social theories and argue for the relevance of mobilities paradigm in the study of indigenous peoples. We belief that a more inter-disciplinary understanding of indigenous peoples would lead to enriched insights into indigenous communities' social and cultural dynamics and provide a new approach to address sustainable development of communities within the increasingly interconnected world.